INTERACTIVE MULTIMEDIA DESIGN OF “JATAKA BOROBUDUR TEMPLE’S RELIEF“ AS A LEARNING MEDIA FOR ELEMENTARY SCHOOL STUDENT - Maskur, Abdul; Harto, Dwi Budi; Wibawanto, Wandah (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
Indonesia is a country that has many cultural preservation. One of the cultural heritages in Indonesia is Borobudur Temple. As a form of cultural heritage, visually Borobudur Temple has reliefs containing messages carved on the walls of the temple. One of the reliefs contained in the carved walls of the Borobudur Temple is the Jataka relief which tells about Bosshisatva both as humans and animals who always exemplify the truth. Therefore, the writer tries to transform some of the stories contained in the Jataka relief into interactive multimedia for elementary school children. In developing the exploration of ideas and forms of work taken from several stories contained in the Jataka reliefs namely monkey & buffalo stories, Ruru Deer stories, and lion & woodpecker stories through several processes namely Preliminary Plan, Pre-production, Production Process, and Post-Production. This study project produces interactive multimedia works in the form of Android applications with a resolution of 1280 x 720 pixels in which there are interactive stories, learning, and simple games.